2019
DOI: 10.1044/2019_jslhr-l-18-0388
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Sentence Recall and Past Tense Measures for Identifying Children's Language Impairments

Abstract: Purpose Measures of linguistic processing and grammatical proficiency represent strong candidates for adaptation into language screeners for early elementary students. One key barrier, however, has been the lack of consensus around the preferred reference standard for assigning affected status. Diagnostic accuracies associated with sentence recall and past tense marking index measures were examined relative to 5 different reference standards of language impairment: receipt of language services, cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…Plante and Vance (1995) judge screening tests to be good if their sensitivity is at least 90% and their specificity is at least 80%. Thus, in the evaluations of the Redmond (2005) sentence recall task conducted independently by Archibald and Joanisse (2009) and Redmond et al (2019) with two different large samples, specificity was good, but sensitivity was lower than desired. That does not mean that the task is not useful.…”
Section: A Solutionmentioning
confidence: 96%
See 2 more Smart Citations
“…Plante and Vance (1995) judge screening tests to be good if their sensitivity is at least 90% and their specificity is at least 80%. Thus, in the evaluations of the Redmond (2005) sentence recall task conducted independently by Archibald and Joanisse (2009) and Redmond et al (2019) with two different large samples, specificity was good, but sensitivity was lower than desired. That does not mean that the task is not useful.…”
Section: A Solutionmentioning
confidence: 96%
“…When a standard score lower than 86 on the CELF-4 was used to identify cases and performance below the 10th percentile on the screener was considered the pass/fail cutoff, the sensitivity of the sentence recall task was .846, and the specificity was .903. Redmond et al (2019) administered the Redmond (2005) sentence recall task to 1,060 students in Grades K-3; 254 participated in more extensive follow-up testing to determine cases of DLD. When a standard score lower than 80 on the CELF-4 was used to identify cases, the sensitivity of the sentence recall task was .878, and the specificity was .887 (Redmond et al, 2019).…”
Section: A Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few recent studies have evaluated researcher-administered protocols that suggest the promise of universal screening for language. For example, Redmond et al (2019) found that individually administered screens involving sentence repetition and past-tense elicitation tasks have high sensitivity and specificity against a range of reference standards for language impairment (see also Archibald & Joanisse, 2009). Whereas Redmond et al's study focused on monolingual English speakers, Pratt et al (2020) demonstrated the utility of sentence repetition tasks as a screen for language impairment in bilingual Spanish-English students (see also Gutiérrez-Clellen et al, 2006).…”
Section: Universal Screeningmentioning
confidence: 99%
“…In fact, children with SLI follow similar growth trajectories to their age peers across different dimensions of language early in childhood, followed by a leveling of rate of growth in pre-adolescence as do their age peers, leaving the children with SLI with a lower-than-expected level of language as they transition into adulthood ( Rice, 2012 , 2019 , 2020 ; Rice & Hoffman, 2015 ). A second conclusion is that certain properties of grammar (best documented for finiteness marking in morphosyntax in languages such as English and many other languages, but certainly not all) are reliable clinical markers of SLI, meeting standards of sensitivity and specificity for identification of affected children, especially well documented for the age range of 3–9 years ( Redmond et al, 2019 ; Rice, 2019 , 2020 ; Rice & Wexler, 2001 ).…”
Section: Legacy Research In Children With Slimentioning
confidence: 99%